Electroacupuncture on the Scalp over the Motor Cortex Ameliorates Behavioral Deficits Following Neonatal Hypoxia-Ischemia in Rats via the Activation of Neural Stem Cells - Da Hee Jung; Malk Eun Pak; Hong Ju Lee; Sung Min Ahn; Young Ju Yun; Yong-Il Shin; Hwa Kyoung Shin; Seo-Yeon Lee; Byung Tae Choi (Life, 2020)
Electroacupuncture (EA) therapy via alternating current stimulation on the scalp over the motor cortex is used for the treatment of brain disorders. Perinatal hypoxia-ischemia (HI), a brain injury in newborns, leads to long-term neurologic complications. Here, we investigated whether EA could promote functional improvements and neurogenesis in a neonatal HI rat model. A neonatal HI rat model was induced by permanent ligation of the left carotid artery in postnatal day 7 pups. EA for neonatal HI rats was performed at 2 Hz (1, 3, or 5 mA; 20 min) from 4–6 weeks after birth. HI rats undergoing EA had improved motor and memory function, with the greatest improvement after 3 mA EA. The corpus callosum was significantly thicker and showed a significant increase in proliferating astrocytes in the 3 mA EA group. We observed proliferating cells and a greater number of newly developed neurons and astrocytes in the subventricular zone and dentate gyrus of the 3 mA EA group than in those of the HI group. These results suggest that EA promotes functional improvements following neonatal HI assault via the proliferation and differentiation of neural stem cells. This effect was the strongest after 3 mA EA, suggesting that this is the optimal treatment dose.